AMMI and stability analyses of bunch mass in multilocational testing of Musa germplasm in sub-Saharan Africa - Ortíz, R. (1998)
There is a genuine need within a plantain and banana (Musa spp.) breeding program to assess thoroughly the experimental materials through a sequence of trials. This will result in the selection of promising clones as potential new cultivars in the targeted agroecozone. Stability analyses and the additive main effects and multiplicative interaction (AMMI) model provide together a means for the identification of clones with 1) homeostatic responses to environmental changes, 2) a genotypic response to environmental changes, and 3) adaptation to specific niches. Fourteen polyploid clones (10 tetraploid hybrids and 4 triploid cultivars) were evaluated in a broad range of environments in sub-Saharan Africa to determine the value of stability and AMMI analyses in Musa trials. The interpretation of the results, especially those concerning the genotype × environment interaction, was facilitated by the combination of stability and AMMI analyses. Tetraploid hybrids combining heavy and stable bunch mass were identified. The results also suggested that a clone should be assessed in the ratoon cycle because plantain and banana are perennial crops. Likewise, high yielding clones with specific adaptation should be selected in environments showing the respective environmental or biotic stress.